An activatable fluorescent probe for monitoring the up-regulation of peroxynitrite in drug-induced hepatotoxicity model. (July 2022) - Su, Huihui; Wang, Nannan; Zhang, Jian; Lu, Xiaoyan; Qin, Shuchun; Wang, Jiamin; Zhao, Weili; Wang, Jianhong
Abstract: The liver, which is an important internal organ and digestive gland of the human body, plays essential roles in metabolism and detoxifictaion. Due to frequently expose to toxic substances, the liver is susceptible to injury. Peroxynitrite (ONOO − ) is a kind of ROS/RNS, which generally formed by the diffusion-limited reaction of O2 ‒ and NO. Some evidences have been confirmed that the production of ONOO − was related to the drug-induced liver injury (DILI). Therefore, developing accurate analytical methods for detecting ONOO − of DILI-related diseases will further ascertain the mechanisms of drug-induced hepatotoxicity. In this work, probe BDPP with fast reponse, high selectivity and good senstivity was successfully constructed and utilized for detecting peroxynitrite in live cells and zebrafish. What's more, in the APAP-induced hepatotoxicity model cells, the probe BDPP could detect the up-regulated expression of ONOO − and evaluate the remediation of NAC. The probe BDPP may as a promising tool for the detection of ONOO − during drug-induced hepatotoxicity related assays. Graphical abstract: Image 1 Highlights: A novel BODIPY-based probe BDPP for selective and sensitive detection of ONOO − was designed and synthesized. BDPP could monitor exogenous and exogenous ONOO − in live cells as well as in zebrafish. BDPP could trace the up-regulation of ONOO − in the APAP-Induced hepatotoxicity in different cells.